Evaluation of a Pseudo-R2 measure for panel probit models - Martin Spiess (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
A simulation study designed to evaluate the pseudo-R2 proposed by Spiess and Keller (1999) suggests that this measure represents the goodness-of-fit not only of the systematic part, but also of the assumed correlation structure in binary panel probit models.
Keywords: 330; Probit-Modell; Maßzahl; Simulation; Theorie